Privatização mercantil da educação superior em contexto de regulação transnacional – o caso FAMA/KROTON do Amapá, Brasil - Nogueira, Heryka Cruz (2020)
This work brings as a research problem the socio-political scenario in which the policies for higher education in Brazil are currently established, particularly regarding the implications of the processes of transnational regulation and market privatization in the reconfiguration of the national system that organizes the sector, in this step unveiling the development trends and impacts on the country. Take the case of Faculdade de Macapá (FAMA), state of Amapá, for empirical study, focusing on the political-institutional and pedagogical reconfiguration that it experienced after its acquisition by the Brazilian private educational conglomerate Kroton Educacional. The guiding question of the research was: What are the changes produced in the institutional policy and in the academic management of the Faculty of Macapá after being acquired by Kroton? From this main question, other questions arose that required further study in the form of secondary questions: What are the macro-political foundations that have guided transnational regulation in the construction of national policies for higher education in the last three decades? What are the legal and market mechanisms used by educational companies to establish their private-market participation in Brazil? That said, the general objective of the research was to understand the change processes applied to FAMA / Kroton in its private- mercantile constitution, in two keys: institutional policy and academic management. In order for the general objective of this work to be achieved, an attempt was made to approach more specific objectives, namely: To analyze the political foundations of the transnational regulation processes that have guided the field of Brazilian higher education policies in recent decades; analyze political speeches and legal practices that have acted in the direction of privatization of a commercial nature in the sector. It is a qualitative research, at the same time bibliographic, documentary and empirical. In addition to the literature review on the recent policy for Brazilian higher education, the review of public documents of the institutions involved and the legislation for the sector, semi-structured interviews were conducted with managers and teachers who experienced the process of changes in FAMA after its incorporation by Kroton. In the analysis of the collected data the Categorical Analysis technique was used and the theoretical references of the study are in the field of Political Sociology of Education, with emphasis on the analytical categories Transnational Regulation, Mercantile Privatization and Academic Management. The thesis defended in this work is that the process of private-mercantile reconfiguration of the Brazilian higher education system tends to institute a corporate, pragmatic and functional institutional policy pattern to the accumulation system. The main conclusions of the study lead to the affirmation of this thesis, given that academic research and interview data indicate that both institutional policy and academic management processes aim to adapt the acquired institution to objectives of a marketing nature.